Geochemistry of Water and Gas Emissions From Cuicocha and Quilotoa Volcanic Lakes, Ecuador - Melián, G. V.; Toulkeridis, T.; Pérez, N. M.; Hernández, P. A.; Somoza, L.; Padrón, E.; Amonte, C.; Alonso, M.; Asensio-Ramos, M.; Cordero, M. (Frontiers in Earth Science, 2021)
We report herein the results of CO2 efflux surveys carried out at Cuicocha and Quilotoa volcanic lakes (Ecuador) with the aim of evaluating the temporal variation of diffuse CO2 emission and its relationship with volcanic activity during 2012-2018 for Cuicocha and 2014-2018 for Quilotoa volcanic lakes. Cuicocha and Quilotoa are the two most active volcanic lakes in Ecuador, and their monitoring is a priority task due to a considerable population density around both lakes. CO2 efflux measurements have been conducted at the surface of the lakes by means of the floating accumulation chamber method. To study the possibility of water stratification and CO2 accumulation in the lakes, vertical profiles of the water column were also conducted at Cuicocha (max. depth 80 m) and Quilotoa (max. depth 170 m) volcanic lakes in 2017 and 2018 respectively. The chemical and isotopic data shows that the lake water receives injections of deep hydrothermal water and gases during periods of intense volcano-seismic unrest. The distribution of the dissolved gas composition along the vertical profiles revealed that CO2 is the most abundant gas species. The carbon isotope signature indicated a clear endogenous origin for CO2, with a greater contribution in the stratification zone in both lakes. The computed diffuse CO2 output for Cuicocha volcanic lake (3.95 km2) showed a range from 53 to 652 t·d-1 for the period 2006-2018, while for Quilotoa volcanic lake (3.50 km2) from 141 to 536 t·d-1 for the period 2014-2018. Between the end of 2011 and the beginning of 2012, an increase in the seismic activity with an episode of long-period seismicity was recorded in Cuicocha volcanic lake, coinciding with the maximum value of diffuse CO2 emission registered in this study. A bathymetric study was carried out in Quilotoa in 2017, giving further information about the degasification processes and the morphology of the lake bottom. This work demonstrates the need to conduct regular surface degassing studies as an important volcanic surveillance tool to understand the processes that take place in the magmatic-hydrothermal system, to be able to better forecast future episodes of volcanic unrest, and to mitigate volcanic risk.